A study on nutritional agents associated with leg lameness in commercial broiler chicken - S, VIJAY AVINASH; KUMAR, RAJA; D, UMA MAHESWARI; D, RAJENDRAN; S, UMA; S, POOBITHA; W, LAKKAWARA; NAIR, M G (The Indian Journal of Animal Sciences, 2026)
This study aimed to investigate the occurrence of leg lameness in commercial broilers and the nutritional agents associated with this condition. The study was carried out during the period from October 2022 to March 2023 in and around Puducherry. A total of 20 commercial broilers farms were investigated for the occurrence of lameness based on the gait scoring system. Birds with a score more than 3 were considered as lame bird. Out of 20, 10 farms with highest occurrence of lameness were selected for further study. The average percentage of lameness in the surveyed and selected farms was 21.1 % and 25 %, respectively. All the flocks were maintained under deep litter system with the recommended floor space on continuous lighting program and ad libitum feeding. None of the flocks showed lesions of foot pad dermatitis and hock burn. Though, the level of calcium and phosphorus did not differ significantly in the feed sample, magnesium and manganese contents were found to be below the recommended level of BIS, 2007. All the feed samples were positive for aflatoxin and in 50% of the samples, the level exceed 20 ppb. No significant difference was recorded in the mean values of serum phosphorous, ALT, AST and glucose between control and lame group but the serum calcium and vitamin D3 were significantly lower in latter. Bone mineral profile revealed relatively lower dry fat free bone weight and ash weight for lame group compared to control group. The bone manganese content was significantly lower in lame birds compared to the control group. The present study highlighted the importance of feeding adequate levels of manganese in the diet of broilers. In addition, the feed should be routinely screened for the levels of aflatoxins.